Improving English in Riyadh Schools through Multimodal Learning and Student Engagement - Renno, Inas (2025)
One of the most important aspects of school is learning methodologies. However, a number of teaching methods have not changed over time in the Kingdom of Saudi Arabia (KSA), impeding meaningful advancement. Few studies have been done on improving teaching strategies in Riyadh, especially in international schools at the upper secondary level. By assessing existing teaching strategies in English classes at the higher secondary level in Riyadh using metrics like student engagement and English competency, this study seeks to close that gap. Due to the lack of MLS use in Riyadh schools, the assessment's goal is to identify potential strengths and weaknesses of the current learning scenario in order to achieve the necessary improvement of English proficiency, which is connected to one of KSA Vision 2030 objectives in the education sector. Higher secondary teachers in Riyadh's international schools made up the study's population as a whole, and data was gathered using questionnaires. The study's research design is a correlational survey study using a quantitative research approach. For quantitative data, descriptive statistics were used. The results demonstrate that while MLS use increased students' interest, inventiveness, and involvement in English classes, its absence had a detrimental impact on their English competence. English teachers, educational planners, and textbook developers can incorporate several MLS modes because of this research's important significance in determining students' engagement and English competency.